CARACTERIZAÇÃO DO RESVERATROL COMPLEXADO À HP-β-CD E O EFEITO DESTE COMPLEXO SOBRE PARÂMETROS DO METABOLISMO ENERGÉTICO EM RATOS HIPERGLICÊMICOS - Nishihira, Vivian Shinobu Kishimoto (2013)
The use of nanoparticles (NPs) as drugs carriers has been widely studied, among these NPs are highlighted the cyclodextrins (CDs), they are cyclic oligosaccharides composed of glucose residues with hydrophobic cavity and a hydrophilic external surface, which enables the formation inclusion complexes with lipophilic substances such as resveratrol (RSV) thereby increasing their solubility in water. RSV is a polyphenol founded in products derived from plants, for example, in the grape skins has been extensively studied for its antioxidant properties, anti-inflammatory, as well as their estrogenic effects in the prevention and treatment of various metabolic disorders, including, Diabetes. The aims of this study were to characterize the complex of RSV in HP-β-CD, validate the method on UV/vis spectrophotometer and after the in vitro treatment, comparing the effect of oral administration of free RSV and complexed with HP-β-CD (Hidroxypropil-Beta-Cyclodextrin) for two months, dose giving of 1 mg RSV / kg rat / day, on the enzyme activity of energy metabolism, pyruvate kinase (PK), creatine kinase (CK), adenylate kinase (AK), in tissue such as kidney, liver, heart, cerebral cortex and hippocampus and lactate dehydrogenase (LDH) in cerebral cortex and hippocampus, some of these compromised in diabetes. And also examine the toxicity and hypoglycemic effect of the complex through biochemical serum parameters. With the characterization been demonstrated that complexation was successfully. On the other hand, with to validate method, the analytical parameters studied indicate a simple, fast and precise, accurate and can be applied safely and reliably to determine the level of RSV incorporated into the inclusion complex. The hypoglycemic effect of RSV glycemic was not observed in our study when treated with both free RSV and complexed RSV. All diabetic groups showed elevated levels of urea, which may have derived from protein catabolism of DM1, however, no increase in the levels of creatinine, a marker of renal injury. Moreover, almost all results of the activities PK, AK, and CKmit CKcit showed no significant difference, indicating again that the kidney tissue is not compromised. Lipidemics levels are associated with vascular injury in DM1. High concentrations of triacylglycerol (TG) and very low density lipoprotein (VLDL) for diabetic groups were reversed by the complex and did not occur with free RSV. This lipid imbalance seems to be due to liver dysfunction, because the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST) and albumin are not altered in diabetic control. All diabetic groups showed significant increases in the activity of alkaline phosphatase (ALP). Several parameters were not affected after two months of treatment as albumin, high-density lipoprotein (HDL), uric acid, direct bilirubin (DB), total bilirubin (TB), total protein (TP), calcium (Ca), iron (Fe) and phosphate. Insulin stimulates the functioning of the liver PK in the absence of this hormone, a feature in DM1, the liver PK activity is reduced in all diabetic groups characteristic inhibition by insulin deficiency, both free RSV and the complex did not revert this situation, which can be proven by hyperglycemia and elevated serum concentration of fructosamine. In the heart, the administration of the complex reduced the activity of PK in diabetic rats and CKcit, but increased the activity of CKmit. The complex also reduced the activity of PK and CKcit in the cerebral cortex of normoglycemic animals. In the hippocampus, the activity of PK is high for all hyperglycemic animals in all diabetic groups and these complexes reinforce this elevation. For the diabetic groups in this tissue, the free RSV strongly reduced activity in both fractions of CK complex and reduces the activity of CKcit. For the diabetic group, RSV also inhibits CKmit complex and inhibits the activity of CKcit though both reductions appear to be offset by an increase in the activity of PK. Catches the attention that HP-β-CD significantly reduces the activity of AK compared to the two controls: diabetic and non diabetic.It is concluded that despite the complex does not affect biochemical markers of toxicity such as creatinine, urea, AST and ALT, it reduces the activity of key enzymes of energy metabolism in various organs, wich can alter cellular energy homeostasis. These findings reinfore the need to evaluate the mechanisms of action of nanoparticles.